Evaluación de los criterios de calidad de energía eléctrica en la Empresa Induce del Ecuador. - Merino Coca, Bryan Alexander (2023)
The present study was carried out in the company "INDUCE DEL ECUADOR" located in the city of Latacunga, Aláquez parish, Tandalivi sector via Mulaló and dedicated to the manufacture and commercialization of finished iron products nationwide. The purpose of this analysis is to carry out the study of the power quality of the electrical system of the company "INDUCE DEL ECUADOR" that presents disturbances in the low voltage system coupled to the secondary of the 100 KVA transformer, which feeds the different areas of the company. Through a bibliographic review and field research, the data on installed load, type of conductors, distance of conductors, protections, among others, was collected.